Kapferer's Brand Identity Prism Analysis on Brand Stord to Increase Brand Awareness - Winata, Karina Sanggraeini Kusuma; Adiwaty, Mei Retno (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to find out the extent of STORD brand identity development using Kapferer's brand identity prism method. The data used in this article is interview data and direct observation through Instagram. The result of this research are each dimension has a different implementation. the physical dimension is depicted in the logo and brand colour pallete, the personality is represented in the style of speech used in Instagram, the relationship is drawn in the CSR program, the culture is depicted in the vision and mission and brand values, the self-image is in the values that STORD always carries, the last reflection is developed through Instagram content. STORD needs to strengthen several dimensions through social media campaigns and content creation.